(untitled) (Swiss Medical Weekly, 2019)
INTRODUCTION “Behavioural and psychological symptoms of dementia” (BPSD) refers to a heterogeneous group of clinical manifestations related to dementia, including apathy, depression, anxiety, delusions, hallucinations, sexual or social disinhibition, sleep-wake cycle disturbances, aggression, agitation and other behaviours considered inappropriate. Because of the complexity and heterogeneity of BPSD, as well as the fragility and multimorbidity of the elderly, pharmacological treatment appears to be limited in terms of safety and efficacy, and nonpharmacological therapies are today considered the first choice. There is growing evidence that interventional approaches such as electroconvulsive therapy (ECT), repetitive transcranial magnetic stimulation (rTMS), transcranial direct current stimulation (tDCS), deep brain stimulation (DBS), and vagus nerve stimulation (VNS) could be safe and efficient options for several psychiatric illnesses in a population presenting resistance to and/or intolerance of pharmacotherapy. AIMS The aim of the present work is to provide a qualitative review of the state of the art in interventional psychiatry in the treatment of BPSD. A particular focus will be on depression and agitation, which represent major stressors on caregivers and a primary cause of institutionalisation. CONCLUSIONS ECT is probably the most promising interventional procedure needing further investigation in order to obtain specific protocols and a consensus on indications. Preliminary data on rTMS, tDCS, and VNS are encouraging although randomised controlled trials to investigate and compare their efficacy in the treatment of BPSD are still lacking. Their feasibility profile could represent an important advantage over ECT. DBS could represent a very effective therapy for behavioural disorders, but knowledge of the precise neuroanatomical targets for BPSD is currently too limited to justify this invasive approach.